Pemetaan Lokasi Rawan Bencana Banjir Berbasis Sistem Informasi Geografis di Kecamatan Babat Kabupaten Lamongan - Hariri, Fauzi; Wisnawa, I Gede Yudi; Atmaja, Dewa Made (Peneliti.net, 2025)
This study aims to map flood vulnerability levels in Babat District, Lamongan Regency, using a scoring and overlay method based on Geographic Information Systems (GIS). Six parameters were analyzed, including rainfall, slope, soil type, land use, elevation, and river buffer. The results classified the area into four vulnerability levels: not vulnerable, moderately vulnerable, vulnerable, and highly vulnerable. The highly vulnerable class dominates with an area of approximately 2,850.10 ha (44.18%), followed by the vulnerable class covering ±2,697.93 ha (41.79%), moderately vulnerable ±802.75 ha (12.44%), and not vulnerable ±107.62 ha (1.59%). The main contributing factors to flood vulnerability are flat topography, alluvial soil characteristics, high rainfall, and proximity to the Bengawan Solo River. The resulting vulnerability map is expected to serve as a reference for local governments and communities in developing flood mitigation strategies and supporting spatial planning in Babat District.